Call Signs of Ukrainian Military in the Language of Mass Media: Functional-Semantic Aspect - Navalna, Maryna; Kostusiak, Nataliia M.; Stanislavchuk, Nataliia; Kapeliukh, Dmytro; Kushch, Nataliia; Demeshko, Inna (My University, 2025)
The article studies the call signs of Ukrainian military personnel, attested in the language of mass media during the period of the full-scale Russian-Ukrainian war (2022–2025). The sources of the analyzed material were all-Ukrainian and regional mass media. Bythe goal, the functional and semantic features of military call signs were studied, with an emphasis on the continuity of trends and the latest manifestations of nominations. The achievement of the goal was facilitated by solving the following tasks:1) to characterize the linguistic parameters of call signs in Ukrainian linguistics; 2) to outline the relevant extralinguistic factors that influence the creation of thenominations under study; 3) to identify thematic groups structured by military call signs of different form and meaning; 4) to analyze the degree of openness of the specified group of anthroponyms that function in the language of Ukrainian mass media in 2022–2025. The analysis of the collected material and the results of the study show that during the full-scale Russian-Ukrainian war, the trend towards the creation of military call signs continues. Lexemes of this variety form the following thematic groups: designation of persons by profession, type of activity, occupation, position; namesthat characterize the bearer by external signs and character traits; nominations that express ethnicity, place of birth, residence, and other geographical concepts; anthroponyms, the basis of which is formed by zoolexemes and botanical names; nominations formed from mythonyms; lexemes that mark tools, objects, and parts of various structures; anthroponyms formed from names and toponyms; nominations of literary characters and film heroes; lexemes assigned to the expression of sweets, desserts, etc. It wasfound that among the corpus of collected material, the largest group is constituted by unofficial names formed from mythonyms and biblical names. Focusing on previous developments made it possible to state that call signs for female soldiers were added, among which there are attested lexemes for the designation of various types of snakes, objects of the solar system, representatives of flora and fauna, mythological images, and parts of various types of weapons. In addition, call signs are assigned to animals. Differentiation of anthroponyms built based onpolysemantic words causes difficulties, since without communication with the bearers of secondary names,it is difficult to determine what semantic content constitutes the derivational basis of the nomination. In the language of Ukrainian mass media, several call signs haveopaque semantics;these include digital names. A tendency towards the active use of the lexeme call sign in proper names has been traced. It has been studied that in the corpus of factual material,not only Ukrainian, but also borrowed words are attested. The expression of Ukrainian military call signs is associated with both neutral nouns and marked ones that have pronounced emotive features. The dynamics of informal lexemes towards an increase in the number of factually substantiated and non-standard models of creation indicatea great promising potential of these linguistic units
Keywords: Anthroponym; Call Signs; Extralinguistic Factors; Functionalism; Lexical-Semantic Processe; Mass Media Languag; Nominations; Proper Names; Russian-Ukrainian War; emantics